2011
DOI: 10.1111/j.1571-9979.2011.00300.x
|View full text |Cite
|
Sign up to set email alerts
|

How Valid Is Negotiation Research Based on Student Sample Groups? New Insights into a Long-Standing Controversy

Abstract: Although a considerable amount of research has examined the impact of experience on negotiation behavior and performance, we still know very little about the usefulness of student samples in negotiation research because most studies have compared the performance of inexperienced students with those who had received some kind of extensive negotiation training or with experienced professional negotiators(s). Against this background, we investigate whether the results obtained from trained student samples are gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 38 publications
1
24
0
Order By: Relevance
“…Consequently, we can be relatively confident that the college students in our sample have cognitive structures similar to those of business managers. Of course, we call for future studies to replicate our findings using samples that include real‐life managers or student negotiators with negotiation experience (Herbst & Schwarz, ).…”
Section: Discussionmentioning
confidence: 88%
“…Consequently, we can be relatively confident that the college students in our sample have cognitive structures similar to those of business managers. Of course, we call for future studies to replicate our findings using samples that include real‐life managers or student negotiators with negotiation experience (Herbst & Schwarz, ).…”
Section: Discussionmentioning
confidence: 88%
“…The participants were diverse professionals and students in negotiation and sustainability‐related fields from different world regions. Butler () demonstrated that the outcomes of student subjects matched those of experienced professionals and Herbst and Schwarz () confirmed that students trained in negotiation perform comparably well to professional negotiators. We collected data from 370 participants grouped into 74 teams of five participants at each negotiating table.…”
Section: Methodsmentioning
confidence: 94%
“…With this considered, the study not only contributes to power in negotiation itself but also to the discussion as to whether student-based experiments are appropriate by applying the same negotiation task to a group of students and professional buyers. Herbst and Schwarz [34] have shown that untrained students are outperformed by experienced managers as well as trained students. While our experiment yields comparable evidence, the novelty lies in the negotiation setting.…”
Section: Discussionmentioning
confidence: 99%